An extended technology-organization-environment (TOE) framework for online retailing utilization in digital transformation: Empirical evidence from Vietnam - Tran Hung Nguyen; Xuan Cu Le; Thi Hai Ly Vu (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Digital transformation has profoundly influenced various socio-economic fields and induced retailing firms to utilize digital innovations to maximize business effectiveness in the digital era. The study aims to pinpoint the motivations for online retailing (ORE) adoption and business performance among Vietnamese businesses in the formative digital transformation stage within an extended technology-organization-environment (TOE) framework. The questionnaire-based data are accumulated for this study. Firm respondents are those who have used and increased their familiarity with ORE in Vietnam. All analysis is performed using structural equation modeling (SEM). The results posit that important factors of technological context (i.e., relative advantage, compatibility, and observability), organizational context (i.e., top management support, entrepreneurial orientation, and technological orientation), and the environmental context (i.e., perceived trend, government support, and legal framework) substantially boost ORE adoption. Additionally, firm age is an essential control variable that strongly influences firms' engagement in ORE. Unexpectedly, firm size, competitive pressure, and control variable (i.e., number of employees) do not significantly affect ORE adoption. Besides, ORE adoption serves as an underlying motivation for business performance. Ultimately, theoretical and practical implications are discussed.
Keywords: 650; business performance; digital transformation; online retailing; technology-organization-environment framework; Vietnam